Planktonic Ctenophora of the Madeira archipelago (Northeastern Atlantic) - Gueroun, Sonia Km; Schäfer, Susanne; Gizzi, Francesca; Álvarez, Soledad; Monteiro, João Gama; Andrade, Carlos; Canning-Clode, João (Zootaxa, 2021)
Ctenophores are fragile gelatinous organisms whose diversity and distribution are relatively unknown. For the first time, the occurrence of four planktonic species, namely Ocyropsis crystallina, Eurhamphaea vexilligera, Cestum veneris, and Beroe sp., was reported from Madeira archipelago waters (NE subtropical Atlantic). This report represents the northernmost records in the Eastern Atlantic Ocean for O. crystallina and E. vexilligera.